2016
DOI: 10.1111/eip.12372
|View full text |Cite
|
Sign up to set email alerts
|

Development of social anxiety disorder secondary to attention deficit/hyperactivity disorder (the developmental hypothesis)

Abstract: Social anxiety disorder (SAD) may develop secondary to childhood attention deficit/hyperactivity (ADHD) in a subgroup of the patients with SAD. Patients pass through a number of identifiable stages of developmental pathways to SAD as they grow up. Patients with ADHD have maladaptive behaviours in social settings due to the symptoms of ADHD. These behaviours are criticized by their parents and social circle; they receive insults, humiliation and bullying. After each aversive incident, the individual feels shame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
0
15
0
2
Order By: Relevance
“…In their latest study Koyuncu et al (2016b) suggested that SAD may develop secondary to childhood ADHD in a subgroup of the patients with SAD. Patients with ADHD may develop maladaptive coping behaviours in social settings due to the symptoms of ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their latest study Koyuncu et al (2016b) suggested that SAD may develop secondary to childhood ADHD in a subgroup of the patients with SAD. Patients with ADHD may develop maladaptive coping behaviours in social settings due to the symptoms of ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition increases gradually as the social fears persist and the individual becomes withdrawn. Koyuncu et al (2016b) concluded that, according to this hypothesis, ADHD as the primary disease should be the focus of treatment for these subgroup of patients with SAD. Our result is consistent with this hypothesis that, both probable ADHD and symptom severity of ADHD were related with symptom severity of social anxiety in the present study, even after controlling neuroticism and extraversion, suggesting that although high neuroticism and low extraversion are related with social anxiety symptoms, ADHD may be related with social anxiety symptoms apart from these relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention-deficit/hyperactivity disorder (ADHD), another childhood disorder that extends over adulthood, is an overlooked condition that has high rates of comorbidity with SAD 31. Only recently increasing evidence suggests that the relationship between the two disorders is closer than that was thought before.…”
Section: Other Psychiatric Conditionsmentioning
confidence: 99%
“…Overlapping symptoms may also increase the risk of misdiagnosis 30. Second, as one disorder can cause the emergence of another or worsen its clinical course, detecting and treating the comorbidity increase the opportunity for early intervention 31. Third, comorbidity may result in worse treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%